Two new species of Xyalidae (Monhysterida, Nematoda) from the East China Sea - Wang, Chunming; An, Liguo; Huang, Yong (Zootaxa, 2018)
Two new free-living nematode species of the family Xyalidae Chitwood, 1951 found in the East China Sea are described. Daptonema donghaiensis sp. nov. is characterized by epidermal chords of transparent cells present in most parts of the body; amphideal fovea approximately two times head diameter from anterior body end; L-shaped spicules with cephalate proximal end; tubular gubernaculums; and conico-cylindrical tail with long cylindrical portion. Cobbia heterospicula sp. nov. is characterized by slender body, buccal cavity with one dorsal tooth and two small subventral teeth; amphideal fovea far from the anterior body end; spicules that are paired but unequal in size, with right spicule longer and left spicule shorter; gubernaculums with dorsal apophyses; and conico-cylindrical tail with long filiform portion. An identification key to valid species of the genus Cobbia is given.